Seasonal Variation of Cosmic Ray Intensity Observed by the Oulu Neutron Monitor - Jaesik Jeong; Suyeon Oh (Journal of Astronomy and Space Sciences, 2020)
Muons and neutrons are representative secondary particles that are generated by interactions between primary cosmic ray particles (mostly protons) and the nuclei of atmospheric gas compounds. Previous studies reported that muons experience seasonal variations because of the meteorological effects of temperature. The intensity of neutrons has a typical modulation with various periods and reasons, such as diurnal and solar variation or transient events. This paper reports that cosmic ray particles, which were observed by neutron monitors, have seasonal variations using the daily data at the Oulu neutron monitor. To eliminate the effects of solar activity across time, the daily data were normalized by two different transformations: transformations with respect to the grand mean and yearly mean. The data after transformation with respect to the yearly mean showed more statistical stability and clear seasonal variations. On the other hand, it is difficult to determine if the seasonal variation results from terrestrial effects, such as meteorological factors, or extraterrestrial effects, such as the position of the Earth in its orbit of revolution.